The specialized pediatric palliative care service in Italy: how is it working? Results of the nationwide PalliPed study - Franca Benini; Anna Mercante; Sara Di Nunzio; Simonetta Papa; The PalliPed Working Group (BMC, 2024)
Abstract Background Accurate estimation of the specialized pediatric palliative care (PPC) burden and the definition of the extent and quality of PPC service in Italy represent urgent needs to enable the proper allocation of PPC resources and the definition of prevention and educational plans. The PalliPed project aimed to provide the first comprehensive assessment of the characteristics of Italian patients requiring PPC, the quality and extent of regional PPC networks/facilities, and the number of dedicated resources. In this paper, we present the results of the second part of the project, regarding the implementation and quality of PPC services in Italy. Methods The PalliPed study had an observational cross-sectional design. All Italian specialized PPC centers/facilities were invited to participate in the project and complete a survey on the characteristics of PPC centers/facilities in different care settings, reporting data as of 24 October 2022. Data were collected online. Results 19 PPC specialized centers/facilities from 12 Italian regions and two autonomous provinces responded to the survey. Among them, 11 are regional referral centers. Seven Italian regions out of 20 reported no PPC centers/facilities, mainly in central-southern Italy. Less than half (45%) of the regional referral centers cover the entire regional territory, and three offer 24/7 service. Ten centers have a dedicated team. Half of the eight non-referral centers offer 24/7 service and have a dedicated team. A total of 1,092 patients were reported by 18 centers as of 24 October 2022. Over the years, an increasing number of patients has been reported, rising from 1,202 (2019) to 1,544 (2021). The dedicated staff is inadequate, and most healthcare providers are not recognized at an institutional level. A shortage of 'young' staff and a lack of specific training was reported, particularly among nurses (77% had no training in PPC). Conclusions The results obtained show how training, information, and research interventions are still necessary for the reorganization of the available resources and definition of proper strategies to respond dynamically to the new emerging needs of these populations. At the same time, our study represents a first step in defining a national registry of PPC models, useful for monitoring evolutions, and critical issues and planning any new or corrective strategy.